Vertical Distribution of Nitrate, Phosphate, and Abundance of Planktonic Diatoms in Pandan Waters, Tapanuli Tengah Regency, North Sumatra - Aritonang, Simon Hasintongan; Siregar, Yusni Ikhwan; Nurrachmi, Irvina (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
This research was conducted in February 2021 in Pandan Waters, Central Tapanuli Regency, North Sumatra Province. The purpose of this study was to analyze the concentration of nitrate and phosphate, analyze the composition distribution and abundance of planktonic diatoms, and analyze the relationship between nitrate and phosphate concentrations with an abundance of planktonic diatoms at different depths in Pandan Waters. The method used is the survey method. The results of the analysis of vertical concentrations of nitrate and phosphate in Pandan waters tend to increase with increasing depth, while the results of vertical analysis of planktonic diatom abundance in Pandan waters tend to decrease with increasing depth. The results of a simple linear regression test showed that the relationship between nitrate concentration and abundance of planktonic diatoms at different depths had a strong (negative) relationship, while the relationship between phosphate concentration and planktonic diatom abundance at different depths had a very weak (negative) relationship